STYGMAT CYPRIANA NORWIDA Z PERSPEKTYWY FILOZOFII DIALOGU EMMANUELA LEvINASA - Kosmala, Marta (Colloquia Litteraria, 2019)
Cyprian Norwid’s Stygmat from the perspective of Emmanuel Levinas’s philosophy of dialogue This study is an attempt to read Cyprian Norwids Stygmat anew, employing a deepened perspective that comes from Emmanuel Levinas’s philosophy of dialogue. First, the author points to the convergence of the poet’s and the philosopher’s views, especially when it comes to the special place occu- pied by the man, interpersonal relations, and effort. While reconstructing the plot of the novella, the author analyzes relationship between principal characters - Oskar and Róża, and Oskar and the Narrator; he pays atten- tion to the issue of effort and openness towards the other person in forging a relationship. Using Levinas’s terminology, the author describes Oskar’s condition - separation and disintegration of his identity - which made it impossible for him to carry the burden of responsibility for the encounter with the other person. This applies to the Narrator as well; he does not fulfill the role of the confidant - as selected for the role by Oskar - nor does he find fulfilment as a writer. The Narrator remains a passive observer of the events, which his conversation with Redaktor testifies to. As far as the ending of the novella is concerned the author turns to irony (very characteristic of Norwid) and the difficulty in distinguishing between moments in which the poet expresses serious and true statements and those with ironic flair.